2020
DOI: 10.1038/s41598-020-75929-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm activity of flavonoids on staphylococcal biofilms through targeting BAP amyloids

Abstract: The opportunistic pathogen Staphylococcus aureus is responsible for causing infections related to indwelling medical devices, where this pathogen is able to attach and form biofilms. The intrinsic properties given by the self-produced extracellular biofilm matrix confer high resistance to antibiotics, triggering infections difficult to treat. Therefore, novel antibiofilm strategies targeting matrix components are urgently needed. The Biofilm Associated Protein, Bap, expressed by staphylococcal species adopts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 68 publications
1
17
0
3
Order By: Relevance
“…The inability to persist on/in melon leaves which was observed for both DSM 2302 or a sigE mutant of the emetic strain (AH187) that was affected in sporulation but not biofilm formation on melon leaves, indicated a major contribution of sporulation over biofilm formation in facilitating long-term bacterial survival in this ecological niche. Consistent with this, metabolomic analysis demonstrated that melon leaves are scarce in carbon and nitrogen sources and dominated by secondary metabolites, especially flavonoids, known as antibacterials and antibiofilms [52,53,54].…”
Section: Discussionsupporting
confidence: 52%
“…The inability to persist on/in melon leaves which was observed for both DSM 2302 or a sigE mutant of the emetic strain (AH187) that was affected in sporulation but not biofilm formation on melon leaves, indicated a major contribution of sporulation over biofilm formation in facilitating long-term bacterial survival in this ecological niche. Consistent with this, metabolomic analysis demonstrated that melon leaves are scarce in carbon and nitrogen sources and dominated by secondary metabolites, especially flavonoids, known as antibacterials and antibiofilms [52,53,54].…”
Section: Discussionsupporting
confidence: 52%
“…The mechanism of antimicrobial activity of polyphenols against bacteria can differ and also depends both on the polyphenol type and bacteria species. Among the most important mechanisms of the antibacterial action of polyphenols are [ 58 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]: Reactions with proteins; Inhibition of nucleic acid synthesis by bacterial cells or DNA damage; Interaction with the bacterial cell wall or inhibition of cell wall formation; Alteration of cytoplasmic membrane function, such as modifications of the membrane permeability or fluidity, cytoplasmic membrane damage and—in the result—the membrane disruption; Inhibition of energy metabolism; Changes in cell attachment and inhibition of biofilm formation; Substrate and metal deprivation. …”
Section: Mechanism Of Antibacterial Activity Of Polyphenolsmentioning
confidence: 99%
“…in order to adopt functional amyloid-like structures as scaffolds of the biofilm matrix. Quercetin (111) , myricetin (114) and scutellarein (44) specifically inhibited Bap-mediated biofilm formation of S. aureus and other staphylococcal species [ 97 ] by preventing the assembly of Bap-related amyloid-like structures.…”
Section: Mechanism Of Antibacterial Activity Of Polyphenolsmentioning
confidence: 99%
“…EGCG impairs the assembly of phenol-soluble modulins (PSMs) fibril formation and targets the preformed fibrils for disentanglement [63]. Another study found flavonoids can specifically prevent biofilm-associated proteins (Bap)-mediated biofilms [64]. Additionally, EGCG is shown to interfere with the polysaccharides that form the glycocalyx and bind peptidoglycan impairing the integrity of the cell wall, thereby suggesting that it can affect the initial attachment of biofilm to the surface [52].…”
Section: Discussionmentioning
confidence: 99%